'Misplaced' central venous catheter in a newborn: Reminder of a common congenital anomaly. (April 2021) - Bhattacharya, Deepanjan
Left superior vena cava is the commonest congenital anomaly of systemic venous return. We present the case of a newborn where left jugular venous placement of central venous catheter resulted in cannulation of the left superior vena cava.